Practice patterns and survival outcomes for muscle-invasive bladder cancer: real-life experience in a general population setting - Plouvier, Sandrine D; Marcq, Gautier; Vankemmel, Olivier; Colin, Pierre; Bonnal, Jean-Louis; Leroy, Xavier; Saint, Fabien; Pasquier, David (International journal for quality in health care, 2024)
Abstract Bladder cancer (BC) is a common malignancy in Europe and North America. Among BCs, muscle-invasive BCs (MIBCs) are distinguished, as they require aggressive treatment due to their spreading potential and poor prognosis. Despite its clinical relevance, little information on MIBC in a general population setting is available. This study aims to report practice patterns and survival outcomes for MIBC patients in a general population setting. MIBCs among BC incidence in 2011 and 2012 recorded in a French population-based cancer registry (810 000 inhabitants) were included in the study. Data were extracted from the medical files. Individual, tumour-related characteristics and initial management including diagnostic tools, multidisciplinary team meeting (MDT) assessment, and treatment delivered were described. Cystectomy, chemoradiation, radiotherapy, and chemotherapy were considered as specific treatments. Matching between MDT decision and the treatment provided was detailed. Management practices were discussed according to the guideline’s recommendations. Overall survival (using the Kaplan–Meier method) and net survival (using the Pohar-Perme estimator) were calculated. Among 538 incident BC cases, 147 (27.3%) were MIBCs. Diagnostic practices displayed a relevant locoregional assessment of BC. Almost all cases (n = 136, 92.5%) were assessed during an uro-oncological MDT with a median time from diagnosis of 18 days (first quartile:12-third quartile:32). Discrepancies appeared between MDT decisions and treatments delivered: 71 out of 86 subjects received the recommended cystectomy or chemoradiation (with or without neoadjuvant chemotherapy); 6 out of 11 had the recommended radio- or chemotherapy; and 9 patients did not undergo any specific treatment despite the MDT decision. Cystectomy was the most common treatment performed; the time to surgery appeared consistent with the guideline’s recommendations. Forty people only received supportive care. Still, the 5-year overall and net survival was poor, with 19% (13–26) and 22% (14–31), respectively. The 5-year net survival was 35% (23–48) for people who underwent curative-intent treatments. MIBC management remains challenging even for cases assessed during an MDT. Many people did not undergo any specific treatment. Prognosis was poor even when curative-intent therapies were delivered. Efforts to reduce exposure to risk factors such as tobacco smoking and occupational exposures must be maintained.